Emerging Technological Tools and Post-Pandemic Academic Performance in College Students - Rosaura , Diaz Hinostroza Mary; Hector , Cerna Gonzales Carlos; Alberto, Sosa Daniel; Cristina , Aranda Dextre Carmen; Juan , Borja Torres Rolando; Montenegro , Luz Petronila Blas; Antonio , Manco Chávez José (Journal of Ecohumanism, 2024)
Emerging technological tools have grown over time, especially during the pandemic, when it became evident how they increased their usefulness within the professional and educational environment, due to the need to maintain the continuity of their professional and academic activities. The objective of this study was to determine the relationship between the use of ICT and post-pandemic academic performance in students at a University of South Lima; the methodology used was of basic type and with a cross-sectional and correlational quantitative approach, using a survey with Likert scale applied to 146 students and whose data were processed with the SPSS statistical program to analyze the Pearson correlation between the variables. The results showed a positive and significant correlation of 0.00, with a Pearson correlation coefficient of 0.648 between the use of ICT and academic performance, this is how these results validate and support previous research, the findings affirm that most students present an optimal performance while they use emerging technologies tools, however, there are other findings that present a high percentage of students with a poor use of ICT associated with low academic performance, despite these results, there is still a wide path of research to further explore both variables and the factors involved.